First cytogenetic characterization of Loricaria simillima (Loricariidae, Siluriformes) from Paraná River (Argentina) with emphasis in cytotaxonomy of Loricaria - Benitez, Mauricio Fabián (2016)
Fil: Benitez, Mauricio Fabián. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Instituto de Biología Subtropical; Argentina.